Fusarium branch blight on highbush blueberry in Argentina - Wright, Eduardo Roberto (2014)
In Argentina, highbush blueberry (Vaccinium corymbosum) is grown in Tucumán, Entre Ríos and Buenos Aires provinces. In the 2010 to 2011 cropping season, a new disease with 10% incidence was observed on the foliage of 'Emerald' plants in Concordia, Entre Rios. Symptoms included acropetal blight and premature branch death. Leaves remained attached and showed tan to brown discoloration. A fungal species was isolated from diseased plant parts and identified as belonging to Fusarium section Gibbosum. Based on its growth and pigmentation on potato-dextrose-agar, and characters on carnation leaf-piece agar and Spezieller Nährstoffarmer agar, the strain was identified as Fusarium acuminatum. Additionally, the internal transcribed spacer (ITS) regions of nuclear ribosomal genes were amplified by PCR, sequenced and the DNA sequence was compared with those in GenBank. The NCBI-Blastn search showed 100% identity of the DNA sequence with GenBank Accession No U85533 sequence for F. acuminatum. Pathogenicity was confirmed on wounded branches of potted blueberry plants. To our knowledge, this is the first report of F. acuminatum causing branch blight on highbush blueberry in Argentina and worldwide.